Flavia Teoc, „Perspectiva sofianică în Saga regelui Harald. Studiu privind articularea sensului din unghiul textemelor kenning”, Cluj-Napoca: Casa Cărții de Știință, 2020, 211 p. - RUSU, Daniel (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Perspectiva sofianică în Saga regelui Harald. Studiu privind articularea sensului din unghiul textemelor kenning (The Sophian Perspective in Haralds saga Sigurðarsonar), by PhD Flavia Teoc, proposes an in-depth analysis of the kenning metaphors from a linguistic perspective. Applying the integralist concepts of language theoretician Eugen Coșeriu and the literary Sophian perspective of the author, philologist and philosopher Lucian Blaga, the work offers an alternative interpretation of the meaning and creative process of the skaldic poetry, acquainting the reader with medieval Scandinavian mythology, history, literature, and culture – each component essential for the understanding of the old poetic metaphors. The first chapter begins with an introduction to Coșeriu’s five principles for linguistics as a science of cultures: the principle of objectivity, of humanism, of tradition, of anti-dogmatism and of response/public utility.